2013
DOI: 10.1016/j.neurobiolaging.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in gene expression and promoter usage in aged human brains

Abstract: To characterize the promoterome of caudate and putamen regions (striatum), frontal and temporal cortices, and hippocampi from aged human brains, we used high-throughput cap analysis of gene expression to profile the transcription start sites and to quantify the differences in gene expression across the 5 brain regions. We also analyzed the extent to which methylation influenced the observed expression profiles. We sequenced more than 71 million cap analysis of gene expression tags corresponding to 70,202 promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 72 publications
(81 reference statements)
1
32
0
Order By: Relevance
“…While they can arise from distinct promoter regions clearly separated by long stretches of sequence, alternative TSSs can also occur close to each other within the same promoter region; even subtle alterations in a gene’s TSS have been associated with changes in the expression of downstream genes in Drosophila melanogaster 1920 and mammals21. CAGE-based techniques have already made valuable contributions to our understanding of transcription in model organisms such as, the fruit fly1920, zebrafish22, and human and mouse152324, and specifically in the nervous system, where alternative TSSs appear to play a role in establishing developmental25 and region-specific26 gene expression patterns. However, the potential relevance of alternative TSSs in organizing behavior has, to our knowledge, not been addressed in any organism.…”
mentioning
confidence: 99%
“…While they can arise from distinct promoter regions clearly separated by long stretches of sequence, alternative TSSs can also occur close to each other within the same promoter region; even subtle alterations in a gene’s TSS have been associated with changes in the expression of downstream genes in Drosophila melanogaster 1920 and mammals21. CAGE-based techniques have already made valuable contributions to our understanding of transcription in model organisms such as, the fruit fly1920, zebrafish22, and human and mouse152324, and specifically in the nervous system, where alternative TSSs appear to play a role in establishing developmental25 and region-specific26 gene expression patterns. However, the potential relevance of alternative TSSs in organizing behavior has, to our knowledge, not been addressed in any organism.…”
mentioning
confidence: 99%
“…We present recount-brain , a freely available human brain sample metadata database that pairs with the uniformly-processed RNA-seq data from recount2 enabling researchers to study transcriptomic changes in neurological disease. Our metadata database and reproducible curation approach shows that freely-available data can be cleaned and curated to encourage and facilitate data reuse and increase the value of small studies, such as SRP017933 (Pardo et al, 2013) , and large studies, such as GTEx and TCGA (Hutter and Zenklusen, 2018) , alike.…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira et al investigated the impact of post-mortem interval (PMI) on gene expression using data from multiple tissues of post-mortem healthy donors obtained from the GTEx project (Ferreira et al, 2018) . To exemplify how recount-brain can be used to replicate findings, we identified 10 SRA studies with variable PMI data for a total of 252 samples from 9 publications (Boudreau et al, 2014;Dumitriu et al, 2016;Khrameeva et al, 2014;Labadorf et al, 2015;Magistri et al, 2015;Pardo et al, 2013;Voineagu et al, 2011;Wu et al, 2012) . In their analysis of GTEx and PMI data, Ferreira et al identified genes with significant temporal changes across tissues (Ferreira et al, 2018) .…”
Section: Effects Of Post-mortem Interval On Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations